Implementasi Pengelolaan Lingkungan Hidup Ditinjau dari Undang-Undang Nomor 32 Tahun 2009 dan Fiqh Al-Bi’ah di Asrama Al-Fajr Ma’had Al-Zaytun - Imam Fatkhan Mubin; Siti Ngainnur Rohmah; Taufiqurachman Taufiqurachman (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The implementation of environmental management is an important aspect in shaping ecological behavior within educational settings. Law No. 32 of 2009 emphasizes the responsibility of individuals and institutions to preserve the environment, in line with the principles of Fiqh Al-Bi’ah in Islam. Al-Fajr Dormitory of Ma’had Al-Zaytun serves as an example of this application through the daily activities of its students. This study aims to describe the implementation of environmental management at Al-Fajr Dormitory based on Articles 67–68 of Law No. 32 of 2009 and the Fiqh Al-Bi’ah perspective. Using a descriptive qualitative method through observation, interviews, and documentation, data were obtained from dormitory administrators, students, and relevant literature. The results show that environmental management is carried out through routine activities such as cleaning duties, waste management, facility maintenance, and the prudent use of resources. From the perspective of Fiqh Al-Bi’ah, these practices reflect the values of stewardship (khalifah), trust (amanah), and balance (mīzān). The synergy between state regulations and Islamic principles fosters disciplined, responsible students with strong ecological awareness as part of sustainable environmental development.